Persepsi Masyarakat Terhadap Keselamatan Transportasi Kereta Api - Mutharuddin, Mutharuddin; Kuswati, Atik S. Kuswati S. (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Transportation safehJ a prominent issue lntely. 17iis research was conducted in order to obtnin adescription of perceptions and behmrior of the co1nnz11nihJ /consumers of the rail transport safety.Transport safety culture can be grown in a Wat to strengthen the institutional, clarifiJ regulations,tighten supen1ision and strengthen prosecution/ enforcement. It also develops programs on activecommunihJ participation in maintaining the railwm; infrastructure.Tiiis research is using grrp analysis, where tire nnnlysis cnn he used to nzensure the let l of publicawareness of safety. Tire analyses slzmued lnrgest miemge ml11e ndzieued In; the application of variable5 (seniice attributes), nnmely the instructions/ infomzntion on train schedules are eaSJ to obtninfor 4.111 and the smallest average mlue on 26 variables (behavioral attributes), throwing objects intothe train fire that is equal to 2.526. While the largest m age value for the benefit achieved lnj the 11variables (a ttributes of safety faci.lities), the signs warning! ban, amounting to 4.656 and the smallestmierage value on 29 variables (beluwioral attributes of people wlw perform activities in the landawned rai.lwm;s), such as selling the mlue of 2.436.Keywords: safeti;, rail transport, public perception.